x2 - 18x + 72 = 0 (x - 6)(x - 12) = 0 x ∈ {6, 12}
0.0083
6 + 12 = 18 6 * 12 = 72
0
2x2 - 72 would be factored into (2x - 12)(x + 6) or (2x + 12)(x - 6) To double check, multiply each pair: (2x - 12)(x + 6) = 2x2 + 12x - 12x - 72 = 2x2 - 72 (2x + 12)(x - 6) = 2x2 - 12x + 12 x - 72 = 2x2 - 72
ANSWER: 12 and -6x * y = 72x = 72/y Equation 1x + y = 6 Equation 2Substitute Eq.1 to Eq.2-72/y + y = 6multiply both sides of the equation by yy (-72/y + y ) = 6* y-72 + y2 = 6yy2 - 6y - 72 = 0(y- 12) (y + 6) = 0y = 12 ; y = -6x =-12 ; x = 12Take x = 12 and y = -6
(-1.2,0),(1.2,0)v(0, -72)50x^2-72=0 factor out 22(25x^2-36)=02(5x+6)(5x-6)=0x=-6/5 and x=6/5The average of these two is zero, substitute that into the equation and you get -72.
Suppose n*6 = 72 Divide both sides of the equation by 6: n = 12
x2 - 18x + 72 = 0 (x - 6)(x - 12) = 0 x ∈ {6, 12}
You could do this by staring with the answer:150x2 = 300; 300+72 = 372; 372/6 = 62.(2x + 72)/6 = 62
-6 when you multiply two minus numbers the minus signs cancel each other out so -12 * -6 = 72
Let the length be x+6 and the width be x: (x+6)*x = 72 x2+6x = 72 x2+6x-72 = 0 Solving the above equation with the quadratic equation formula will give: x = -12 or x = 6, so x must be the latter because dimensions can't be negative. Therefore: length = 12 m and width = 6 m Check: 12*6 = 72 square meters
this is not an equation and hence can not be interpreted. Do you mean 72(x) = 7504 implying x = 104.2222...... or 72 x 7504 = 540288
The answer is 432. From the problem you can set up two equations and solve them for your answer x. x/24 = n +6 x/36 = n ... from the second equation we know n = x/36. Plug this into the first equation. then, x/24 = x/36 +6 ... rearranging, x/24 - x/36 = 6 ... finding a common denominator, 3x/72 - 2x/72 = 6 ... x/72 = 6 ... x = 6 * 72 ... x = 432 Your final answer.
72 is divisible by 6. (72 / 6 = 12) Hence 6 is a composite number of 72.
The LCM is: 72lcm(9, 8, 6) = 72
72 / 6 = 12 Therefore 12 * 6 = 72